2008
DOI: 10.1007/s10528-008-9193-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence Among Marine and Lagoon Atherina boyeri Populations in Greece Using mtDNA Analysis

Abstract: Genetic differentiation and phylogenetic relationships among 15 Atherina boyeri populations from several marine and lagoon or lake sites in Greece were investigated using mtDNA analysis. PCR-RFLP analysis of 12s, 16s rRNA genes and D-loop revealed 23 haplotypes. All the lake or lagoon populations, as well as the Kymi and Kalymnos populations that originated from sites with lagoonlike environmental conditions, showed haplotypes 1-6, clearly distinguishable from the marine populations, which exhibited types 7-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 33 publications
2
18
0
15
Order By: Relevance
“…On the other hand, the lack of significance in the AMOVA comparisons between groups could be also due to low power associate with a low number of populations per group such as was described by Fitzpatrick (2009). Therefore, according to our results from F ST values, Cavalli-Sforza genetic distances, correspondence analysis and significant genic and genotypic differentiation, we suggested that the highest genetic divergence observed between samples (Mazarrón and the rest of localities) could be consequence of the isolation of lagoonal populations from open sea which has been already reported in other coastal fishes such as Pomatoschistus minutus Berrebi et al 2009), Dicentrarchus labrax (Lemaire et al 2000), Atherina lagunae (Trabelsi et al 2004), Atherina boyeri (Kraitsek et al 2008;Milana et al 2012), Diplodus sargus (González-Wangüemert and Pérez-Ruzafa 2012) and several invertebrate species (Camilli et al 2001;González-Wangüemert et al 2006;Tarnowska et al 2010;Vergara-Chen et al 2010b).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, the lack of significance in the AMOVA comparisons between groups could be also due to low power associate with a low number of populations per group such as was described by Fitzpatrick (2009). Therefore, according to our results from F ST values, Cavalli-Sforza genetic distances, correspondence analysis and significant genic and genotypic differentiation, we suggested that the highest genetic divergence observed between samples (Mazarrón and the rest of localities) could be consequence of the isolation of lagoonal populations from open sea which has been already reported in other coastal fishes such as Pomatoschistus minutus Berrebi et al 2009), Dicentrarchus labrax (Lemaire et al 2000), Atherina lagunae (Trabelsi et al 2004), Atherina boyeri (Kraitsek et al 2008;Milana et al 2012), Diplodus sargus (González-Wangüemert and Pérez-Ruzafa 2012) and several invertebrate species (Camilli et al 2001;González-Wangüemert et al 2006;Tarnowska et al 2010;Vergara-Chen et al 2010b).…”
Section: Discussionsupporting
confidence: 79%
“…An ecological feature is in favor of this hypothesis for the Kerkennah Islands where the very particular aspect of phanerogames Posidonia oceanica fields named "herbier tigré" constitutes a disrupted habitat which facilitates isolation of several micropopulations: strips of several tens meters long separated by one to two meters wide weave beds of Cymodocea nodosa and Caulerpa prolifera, between 0.5 and 3 m deep [48,49]. Interestingly, a recent study using mtDNA analyses shown evidences that two Atherina populations of the A. boyeri complex sampled from two islands of the Aegean Sea grouped with those of lagoon/lake environments, whereas the other island populations grouped together [11]. According to the authors, this fact could be due to the physical-chemical conditions existing in the sampling sites; indeed, one of them is a small shallow and narrow bay where freshwater is gushing out, whereas in the other there are hot springs and moreover mineral water.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study coupling biometric and mitochondrial DNA (mtDNA) data within this species complex, recognized at least three species: A. boyeri, A. punctata and A. lagunae as respectively non-punctuated marine, punctuated marine and lagoon atherines [5,6]. Moreover, molecular investigations by mtDNA [7][8][9][10][11] and allozyme analysis [12] confirmed our previous hypothesis by which A. boyeri can be considered as a complex of two different species (one marine and one living in lagoons and river mouths) [5,6], punctuated fish were not present in all these last studies. The distribution of A. boyeri species sensu stricto ranges in the Northeast Atlantic from the Azores to the Northwest coasts of Scotland; it is common in the Southern North Sea and the English Channel, less so further north, and being found throughout the Mediterranean and Black Sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion was supported by a biochemical approach by Focant et al (1992Focant et al ( , 1993Focant et al ( , 1999 and by a genetic approach by Cammarata et al (1996), using electrophoresis analysis of a muscle protein and allozymic variation of 20 loci, respectively. More recent investigations also based on allozyme analysis (Mauro et al 2007) and molecular data tended to consider Atherina boyeri a taxonomic complex, divided by some authors into two forms: one lagoon type and one marine non-punctuated type (KlossaKilia et al 2002(KlossaKilia et al , 2007Kraitsek et al 2008). Other authors (Trabelsi et al 2002a(Trabelsi et al , 2002b(Trabelsi et al , 2004Astolfi et al 2005;Milana et al 2008;Francisco et al 2008Francisco et al , 2011 recognised three forms: one lagoon type and two marine types (punctuated and nonpunctuated on the flanks).…”
Section: Introductionmentioning
confidence: 99%